IMPLEMENTASI PENDEKATAN BEHAVIORISME DALAM PROSES TERAPI ANAK BERKEBUTUHAN KHUSUS CEREBRAL PALSY DI RUMAH TERAPI DARUL FATHONAH KUDUS [IMPLEMENTATION OF BEHAVIORISM APPROACH IN THE THERAPY PROCESS OF CHILDREN WITH CEREBRAL PALSY SPECIAL NEEDS AT THE THERAPY HOME OF DARUL FATHONAH KUDUS] - Heny Kristiana Rahmawati (Perkumpulan Ahli Bimbingan Konseling Islam (PABKI) Indonesia, 2021)
This study aims to determine the behavioral approach given by counselors in the field of rehabilitation counseling for children with special needs, especially cerebral palsy in the therapeutic process at Darul Fathonah Kudus Therapy House and to know the application of the counseling. The research method used is a qualitative research method with a field study approach. The findings of this study are the counseling method used by the Darul Fathonah therapy house, namely the individual counseling method with a behavior approach for treatment and development of life competencies such as in terms of cognition and motor skills.